Estereótipos da mulher no discurso de autoajuda - Brunelli, Anna Flora [UNESP] (My University, 2012)
Building on the foundations of French Discourse Analysis and Social Psychology's developments on the issue of stereotypes, this paper analyzes the images of women available in works of self-help for women. With this purpose in mind, we have especially taken into account aphorizing enunciations present in works of this kind currently circulating in the market. The analysis shows the contradiction inherent to the self-help discourse for women, which proposes to women a pattern of behavior consistent with their emancipation, but, at the same time, contributes to keeping certain female stereotypes associated with their traditional roles.
Women's stereotypes in self-help discourse
Keywords: Aphorisation; Self-help discourse; Stereotype; Women